Comparison of the therapeutic efficacy of SNAP-tag fusion protein and the synergistic actions of chemotherapy and photodynamic therapy in killing resistant melanoma - Biteghe, Fleury Augustin Nsole (Department of Integrative Biomedical Sciences (IBMS), 2019)
Cutaneous melanoma is the deadliest form of skin cancer, which arises from epidermal pigment-producing cells called melanocytes. In melanoma, surgical excision of primary nonmetastatic tumor remains the gold standard of therapy worldwide. Upon metastases, melanoma becomes highly resistant to conventional radio-and chemotherapy. Chemotherapy, using dacarbazine (DTIC), remains the standard treatment option. In melanoma, chemotherapy failure has partly been attributed to a resistant population which is endowed with higher clonogenic potential, and aberrant expression of membrane proteins known as ABC transporters (ABCB5 and ABCG2), which mediate cellular resistance by extruding cytotoxic molecules from cells. To palliate these adverse effects, this study primarily aimed to investigate the efficacy of the synergistic actions of chemotherapy (Dacarbazine:DTIC) and hypericin-activated photodynamic therapy (HYP-PDT) in reducing chemoresistance in DTIC resistant (UCT Mel1DTICR2) and non-resistant melanoma cells (UCT Mel-1). To achieve these goals, the therapeutic efficacy of conventional therapies (DTIC, HYP-PDT and DTIC+HYP-PDT) was evaluated based on their ability to reduce cell viability; therapeutic resistant subpopulations; clonogenicity and ABC transporters (ABCB5 and ABCG2) in both melanoma cells. Additionally, the ability of the therapeutic treatments to efficiently halt cell division and activating cell death mechanisms, was assessed using cell cycle analysis and an Annexin-V assay. The results obtained showed that combination therapy was the most efficient therapy which was associated with a reduction in main populations (therapeutic resistant sub-population not expressing ABC transporters: MP), and clonogenic capacity in both melanoma cell types. Similarly, DTIC displayed a therapeutic efficacy which significantly reduced side populations (therapeutic resistant sub-population which were expressing ABC transporters: SP), and clonogenicity in UCT Mel-1 only. Interestingly, both ABCG2 and ABCB5 expressions were significantly increased in both melanoma cells, post combination therapy. Lastly, combination therapy and PDT were equally shown to induce a G1 cell cycle arrest, as opposed to DTIC which induced an S phase arrest. These cell cycle arrests were associated with efficient activation of apoptosis and necrosis, depending on the melanoma cell type, post HYP-PDT and combination therapy. Nevertheless, the efficacy of DTIC and HYP-PDT might respectively be limited by off target effects harming normal cells and low dosage in tumour cells which limiting their clinical utility. To address these challenges, this study aimed to develop a targeted tumor therapy, using the self-labelling activity of SNAP-tag fusion protein to conjugate synthetic small molecule lead substance toxin such as monomethyl Auristatin F (MMAF or AURIF). This cytotoxic payload was delivered to targeted cells, through genetic fusion of SNAP-tag to three different single chain fragments of an antibody (scFv1711, LsFv49 and scFv#34), which specifically treated tumor cells expressing epidermal growth factor (EGFR), melanotransferrin (p97) orfibroblast activation protein alpha (FAP-α) receptors, respectively. Achievement of this targeted therapy was performed through construction of three scFv-SNAP fusion proteins, which were expressed in HEK 293T cells. Thereafter, the purified scFv-SNAP fusion proteins were conjugated to BG-substrates to investigate their efficacy in specifically killing tumor cells. Binding and cytotoxic activities of the scFv-SNAP fusion proteins were performed using flow cytometry, and the XTT cell viability assay. All scFv-SNAP-fusion proteins were specifically bound to their target cells, indicating that AURIF conjugation did not compromise the binding activity of scFv-SNAP fusions. Finally, the cytotoxic assay confirmed that all scFv-SNAPAURIF conjugates induced a 50 percent reduction in cell viability at nanomolar concentrations in targeted cells which expressed their cognate antigens. To conclude, combination therapy was shown to be more efficient than monotherapies in killing chemoresistant melanoma cells, while SNAP-tag technology provided a superior, targeted therapeutic efficacy by sparing normal cells from unwanted toxic effects, and reducing the therapeutic requirement for high concentration of cytotoxic payloads.